Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Solve the boundary value problem $$\begin{cases} \displaystyle \frac{\partial u}{\partial t} = 2 \frac{\partial^2 u}{\partial x^2} \\ \ \\u(0,t) = 10 \\ u(3,t) = 40 \\ u(x, 0) = 25 \end{cases}$$

share|cite|improve this question
This uses separation of variables and Fourier series. I am sure there are many resources you can find online telling you how to solve a problem like this. – nayrb Nov 28 '12 at 16:36

HINT: Let's make the boundary condition homogenous by $v(x,t)=u(x,t)-10-10x$.
(How to see that?). The pde for $v(x,t)$ is thus: (Notice that $v_t=u_t$, $v_{xx}=u_{xx}$, and why?)

$$\begin{cases} v_t - 2 v_{xx} = 0, & 0<x<3, t>0, \\ v(0,t)=v(3,t)= 0, & t\geqslant 0, \\ v(x,0)=15-10x, & 0<x<l. \end{cases}$$

This question should be familiar to you now, as it's got homogenous b.c. and good i.c.. It shouldn't be hard once you find $v$, because you get $u$ the instant you get $v$.

Next: Familiar stuffs: Apply the method of separation of variables, i.e. $v(x,t)=X(x)T(t)$ and solve for the eigenvalues and eigenfunctions. Expand $f(x)=15-x$ into the Fourier series based on the eigenvalues, and solve for the specific result.

share|cite|improve this answer

Let $u(x,t)=X(x)T(t)$ ,

Then $X(x)T'(t)=2X''(x)T(t)$



$\begin{cases}T(t)=c_3(n)e^{-\frac{2n^2\pi^2t}{9}}\\X(x)=\begin{cases}c_1(n)\sin\dfrac{n\pi x}{3}+c_2(n)\cos\dfrac{n\pi x}{3}&\text{when}~n\neq0\\c_1x+c_2&\text{when}~n=0\end{cases}\end{cases}$

$\therefore u(x,t)=C_1x+C_2+\sum\limits_{n=0}^\infty C_3(n)e^{-\frac{2n^2\pi^2t}{9}}\sin\dfrac{n\pi x}{3}+\sum\limits_{n=0}^\infty C_4(n)e^{-\frac{2n^2\pi^2t}{9}}\cos\dfrac{n\pi x}{3}$

$u(0,t)=10$ :

$C_2+\sum\limits_{n=0}^\infty C_4(n)e^{-\frac{2n^2\pi^2t}{9}}=10$

$\sum\limits_{n=0}^\infty C_4(n)e^{-\frac{2n^2\pi^2t}{9}}=10-C_2$


$\therefore u(x,t)=C_1x+C_2+\sum\limits_{n=0}^\infty C_3(n)e^{-\frac{2n^2\pi^2t}{9}}\sin\dfrac{n\pi x}{3}+10-C_2=C_1x+10+\sum\limits_{n=1}^\infty C_3(n)e^{-\frac{2n^2\pi^2t}{9}}\sin\dfrac{n\pi x}{3}$

$u(3,t)=40$ :



$\therefore u(x,t)=10x+10+\sum\limits_{n=1}^\infty C_3(n)e^{-\frac{2n^2\pi^2t}{9}}\sin\dfrac{n\pi x}{3}$

$u(x,0)=25$ :

$10x+10+\sum\limits_{n=1}^\infty C_3(n)\sin\dfrac{n\pi x}{3}=25$

$\sum\limits_{n=1}^\infty C_3(n)\sin\dfrac{n\pi x}{3}=-10x+15$

$C_3(n)=\dfrac{2}{3}\int_{3k}^{3(k+1)}(-10x+15)\sin\dfrac{n\pi x}{3}dx$ , $\forall k\in\mathbb{Z}$ , $x\in(3k,3(k+1))$

$C_3(n)=\left[\dfrac{20x-30}{n\pi}\cos\dfrac{n\pi x}{3}-\dfrac{60}{n^2\pi^2}\sin\dfrac{n\pi x}{3}\right]_{3k}^{3(k+1)}$ , $\forall k\in\mathbb{Z}$ , $x\in(3k,3(k+1))$

$C_3(n)=\dfrac{(-1)^{n(k+1)}(60k+30)-(-1)^{nk}(60k-30)}{n\pi}$ , $\forall k\in\mathbb{Z}$ , $x\in(3k,3(k+1))$

$\therefore u(x,t)=10x+10+\sum\limits_{n=1}^\infty\dfrac{(-1)^{n(k+1)}(60k+30)-(-1)^{nk}(60k-30)}{n\pi}e^{-\frac{2n^2\pi^2t}{9}}\sin\dfrac{n\pi x}{3}$ , $\forall k\in\mathbb{Z}$ , $x\in(3k,3(k+1))$

Hence $u(x,t)=10x+10+\sum\limits_{k=-\infty}^\infty\sum\limits_{n=1}^\infty\dfrac{(-1)^{n(k+1)}(60k+30)-(-1)^{nk}(60k-30)}{n\pi}\prod_{3k,3(k+1)}(x)e^{-\frac{2n^2\pi^2t}{9}}\sin\dfrac{n\pi x}{3}~,~x\in\mathbb{R}$

share|cite|improve this answer
For homework (and, for some of us, suspected homework) we usually give hints instead of a full solution. – Ross Millikan Dec 1 '12 at 3:18

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.